1994
DOI: 10.2166/wst.1994.0301
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics and Nitrite Build-Up in Activated Sludge and Biofilm Processes for Nitrogen Removal

Abstract: This article has the objective of showing the cause effect relationship between the dynamics of growth of autotrophic populations involved in nitrification and the uncontrolled accumulation of nitrite ions. This accumulation results in a disequilibrium in number or viability between the genera Nitrosomonas and Nicrobacter. This disequilibrium can be imposed, for example, by an inhibition of the activity of the genus Nitrobacter linked to the presence of free ammonia in the environment. The threshold of inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2000
2000
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 0 publications
1
18
0
2
Order By: Relevance
“…Whatever the temperature, Mauret et al (1996) observed a transient nitrite build-up of roughly 50% of the initial ammonia concentration for threshold concentrations of FA of 8.91 mg N L −1 . Villaverde et al (2000) and Rols et al (1994) remark that the inhibition phenomenon is specific and depends both upon the concentration of nitrifying organisms Villaverde et al (1997) as upon the threshold concentration (on volume basis) of FA causing inhibition. In doing so, Rols et al (1994) established the threshold of inhibition of NOB between 0.5 and 3 mg NH 3 -N mg −1 viable NOB biomass.…”
Section: Ammonium (Nh + 4 ) or Free Ammonia (Nh 3 )mentioning
confidence: 99%
See 2 more Smart Citations
“…Whatever the temperature, Mauret et al (1996) observed a transient nitrite build-up of roughly 50% of the initial ammonia concentration for threshold concentrations of FA of 8.91 mg N L −1 . Villaverde et al (2000) and Rols et al (1994) remark that the inhibition phenomenon is specific and depends both upon the concentration of nitrifying organisms Villaverde et al (1997) as upon the threshold concentration (on volume basis) of FA causing inhibition. In doing so, Rols et al (1994) established the threshold of inhibition of NOB between 0.5 and 3 mg NH 3 -N mg −1 viable NOB biomass.…”
Section: Ammonium (Nh + 4 ) or Free Ammonia (Nh 3 )mentioning
confidence: 99%
“…Villaverde et al (2000) and Rols et al (1994) remark that the inhibition phenomenon is specific and depends both upon the concentration of nitrifying organisms Villaverde et al (1997) as upon the threshold concentration (on volume basis) of FA causing inhibition. In doing so, Rols et al (1994) established the threshold of inhibition of NOB between 0.5 and 3 mg NH 3 -N mg −1 viable NOB biomass. For the same reason, Suthersan and Ganczarczyk (1986) introduce the FA over biomass ratio as a specific inhibition effect measure.…”
Section: Ammonium (Nh + 4 ) or Free Ammonia (Nh 3 )mentioning
confidence: 99%
See 1 more Smart Citation
“…Il en est de même pour les caractéristiques de la population nitrifiante, d'après les travaux de BALMELLE et al (1992) et ROLS et al (1994. Ces auteurs ont remarqué l'importance de la composition et de l'histoire de la biomasse nitrifiante : en fonction du groupe de bactéries prédominant dans la culture (population mixte ou enrichie en bactéries nitritantes), des réponses différentes aux paramètres environnementaux sont obtenues, les principaux étant les concentrations en NH 3 et en HN0 2 .…”
Section: Synoptic Représentation Of the Nitrogen Biological Treatmentunclassified
“…Cependant, la cause majeure du déplacement est la composition de la biomasse, laquelle est dans notre cas principalement nitratante. ROLS et al (1994) ont montré qu'une culture enrichie en bactéries nitritantes (et donc appauvrie en bactéries nitratantes) présentait plus de sensibilité à NH 3 qu'une culture considérée comme mixte. Le fait qu'une population enrichie en bactéries nitratantes présente dans notre cas une activité respiratoire résiduelle même à 70 mgN-NH 3 /l reste cohérent avec ces observations.…”
Section: Effet De La Concentration En Nhunclassified